Observasi Perkembangan Tradisi Ngabuburit di Kalangan Generasi Muda - Putri, Leony Assyifa; Maghfira, Ashila; Esy, Mariana Luna; Rahmawati, Siti Salma; Fitria, Ratna (Jurnal Ilmu Sosial dan Budaya Indonesia, 2025)
The word ngabuburit is interpreted as relaxing while waiting for the afternoon in the fasting month. Along with the times, the ngabuburit tradition slowly changed, although not significantly. The values of togetherness and simplicity that used to be the core of ngabuburit are slowly fading, displaced by the dominance of digital devices that make social interaction increasingly distanced. This research aims to explain the factors that affect the development of the ngabuburit tradition in the modern era. This study uses a type of descriptive qualitative research. Descriptive qualitative research aims to describe and understand the phenomenon that is researched in depth based on the perspective of the respondents. This research also seeks to explore the social and cultural meaning behind ngabuburit activities in the context of today's young generation. This study presents the latest data and reveals the activities of the younger generation in spending time before breaking the fast or ngabuburit. Different from previous research that discussed more traditional ngabuburit, this study focuses on trends and changes in ngabuburit patterns that emerge among the younger generation during Ramadan. From the results of a survey involving 50 respondents aged 18-21 years, it was found that the most common ngabuburit activities carried out by the younger generation still revolve around walking, and snacks. Even so, there are also those who prefer to spend time at home relaxing or sleeping. When asked about the importance of ngabuburit in undergoing fasting, respondents' responses were quite diverse. Some consider ngabuburit to be an important part of living Ramadan because it helps to divert hunger and maintain mental balance. Meanwhile, others feel that ngabuburit is just an additional activity that does not have much effect on the essence of fasting itself. In the conclusion, the researcher stated that the essence of the ngabuburit activity itself remains the same, namely to be an important moment to refresh the mind and be a self-balancing from daily busyness during fasting.